ON THE SPECIFICS OF PUBLIC-PRIVATE PARTNERSHIP IN RUSSIAN AND FOREIGN PRACTICE - R. Ustaev; V. Parakhina; Z. Shalashaa (Вестник Северо-Кавказского федерального университета)
The article examines the importance of public-private partnership at the current stage of development of the Russian economy. The basic features of the public-private partnership system in a number of leading countries of the world are studied. The specifics of the development of public-private partnership in the Russian Federation are studied, with the identification of General models of this partnership, taking into account the goals and nature of the tasks required for implementation. The importance of developing and using public-private partnership mechanisms in the economy of Abkhazia aimed at improving investment processes, attracting additional resources and improving the quality of services provided in the socio-cultural sphere is emphasized. Potential development opportunities in the sphere of public-private partnership within the framework of international cooperation between Russia and Abkhazia are highlighted. The most common mechanisms and tools used in the implementation of public-private partnership in a number of leading countries of the world are highlighted. The main parameters that influence the choice of public-private partnership model are identiied.